Racial/Ethnic Distribution of Graduates from Doctorate and Masters Epidemiology Degree Programs in the United States, 2008 to 2018. - Gondwe, Tamala; Herbach, Emma; Cvitanovich, Matthew; Begay, Joel; Santee, Endia; Buzzacott, Peter; Hidalgo, Bertha (2021)
PURPOSE: To identify trends in racial and ethnic diversity of epidemiology graduate degree recipients in the U.S. between academic years 2008 to 2018.